2015
DOI: 10.1042/bsr20150122
|View full text |Cite|
|
Sign up to set email alerts
|

Stress-mediated Sin3B activation leads to negative regulation of subset of p53 target genes

Abstract: SynopsisThe multiprotein SWI-independent 3 (Sin3)-HDAC (histone deacetylase) corepressor complex mediates gene repression through its interaction with DNA-binding factors and recruitment of chromatin-modifying proteins on to the promoters of target gene. Previously, an increased expression of Sin3B and tumour suppressor protein, p53 has been established upon adriamycin treatment. We, now provide evidence that Sin3B expression is significantly up-regulated under variety of stress conditions and this response is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The impact of this biological response on tumorigenesis has been studied in detail (Rielland et al, 2014) and elaborated in Section 7. Similarly, levels of both Sin3A and Sin3B increase under conditions of genotoxic stress and have been shown to be important for increasing stability and trans-repressive functions of tumor suppressor TP53 (Bansal et al, 2011;Kadamb, Mittal, Bansal, & Saluja, 2015;Murphy et al, 1999;Zilfou, Hoffman, Sank, George, & Murphy, 2001). Sin3 proteins also interact with retinoblastoma family of tumor suppressors via RBP1 member of the Sin3 complex for repressing transcription of E2F-responsive pro-proliferative genes (Lai et al, 2001).…”
Section: Role Of Sin3 In Cancer-tumor Suppressor or Oncogenementioning
confidence: 96%
“…The impact of this biological response on tumorigenesis has been studied in detail (Rielland et al, 2014) and elaborated in Section 7. Similarly, levels of both Sin3A and Sin3B increase under conditions of genotoxic stress and have been shown to be important for increasing stability and trans-repressive functions of tumor suppressor TP53 (Bansal et al, 2011;Kadamb, Mittal, Bansal, & Saluja, 2015;Murphy et al, 1999;Zilfou, Hoffman, Sank, George, & Murphy, 2001). Sin3 proteins also interact with retinoblastoma family of tumor suppressors via RBP1 member of the Sin3 complex for repressing transcription of E2F-responsive pro-proliferative genes (Lai et al, 2001).…”
Section: Role Of Sin3 In Cancer-tumor Suppressor or Oncogenementioning
confidence: 96%
“…SIN3 also regulates response to stress in both fly and mammalian models. [ 40,42 ] The knockdown of Sin3A in Drosophila leads to reduction in expression of genes encoding proteins required for glutathione synthesis as well as increased susceptibility to oxidative stress, a sensitivity that is rescued by glutathione supplementation. [ 40 ] A study in mammalian cancer cell lines showed that SIN3B is important in the stress response to treatment with different DNA‐damaging agents.…”
Section: The Sin3 Corepressor Regulates Genes Involved In Essential Cmentioning
confidence: 99%
“…[ 40 ] A study in mammalian cancer cell lines showed that SIN3B is important in the stress response to treatment with different DNA‐damaging agents. [ 42 ] Following treatment, there is an increase in expression of SIN3B at the transcript and protein level, which is p53‐dependent. Additionally, when Sin3B is knocked down during damage, p53 target stress response genes are affected, linking SIN3B to the p53‐mediated response to DNA damage.…”
Section: The Sin3 Corepressor Regulates Genes Involved In Essential Cmentioning
confidence: 99%
“…SIN3 interacts with Class I histone deacetylases (HDAC1/2) and accessory proteins forming the SIN3/HDAC chromatin modifying complex [8] . Transcription factors that specifically bind to one or more of the four paired amphipathic helical (PAH1–4) domains of SIN3A provide interface for assembly of multiple proteins [ 9 , 10 ]. These proteins bind to SIN3 via their amino acid sequence specific SIN3-interaction domain (SID) and are known as SID proteins.…”
Section: Introductionmentioning
confidence: 99%